Comparative Study of Single-Port Laparoscopic Cholecystectomy and Four-Port Laparoscopic Cholecystectomy (International Journal of Food and Nutritional Sciences, 2022)
Background: The therapy of choice for benign and symptomatic gallbladder disease is laparoscopic cholecystectomy (LC). Standard laparoscopic cholecystectomy has been linked to a conversion rate of 0.2%, biliary complication rates between 0.26 and 0.6%, and intestinaldamage rates between 0.14 and 0.3%. Major morbidity is related to pain, wound problems, and cosmetic results and is associated with typical LC access ports. Wound-related complications continue to account for over 2.3% of total mortality.Aim’s & Objectives: To assess the feasibility of Single Incision Laparoscopic Cholecystectomy using conventional laparoscopic instruments and compare it with conventional Four port laparoscopic cholecystectomy .Methods & Materials: The prospective randomised control Study was conducted in the Department of General Surgery, Santosh Hospital & Medical College, Santosh University, Ghaziabad from March 2014 to September 2015.There were 60 Patients undergoing Cholecystectomy for Choleliathiasis with 30 in each group.Results: The maximum hospital stay in group I (LC) was 4 days for the patient who developed atelestasis. Whereas in group II (SILC) it was 3 days for patient who developed thrombophebitis. The mean hospital stay in group I (LC) was 1.1 and in group II (SILC) was 1.07. The difference of which was statistically non-significant (p value>0.05).Conclusion: SILC is a safe and feasible procedure which requires a high degree of technical expertise on the part of surgeon. SILC is a promising alternate method to conventional four port laparoscopic cholecystectomy. Although the idea of SILC seems similar to standard four port laparoscopic cholecystectomy, but practically it has major difference in technique. It involves crowding of all working instrument within one incision and the basic principle of triangulation is lost to one extent.